Preparing future psychologists to develop motivational systems - P. Bleshmudt (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
This study aimed to investigate the process of developing motivational systems in aesthetic medicine, as undertaken by future psychology graduates. The methodology involved a combination of modelling and experimentation methods in medical clinics, where the effectiveness of motivational systems created by trainees was tested and evaluated. The research combined theoretical knowledge with practical application, enabling a detailed analysis of how motivational systems can be effectively designed and implemented by future specialists in psychology. The key findings demonstrated that practical involvement in real-world settings, such as medical clinics, significantly enhances trainees’ understanding and ability to develop effective motivational systems. The study revealed that integrating practical experience with a professional environment provides valuable insights that a purely theoretical approach cannot offer. The study confirmed that real-world experience in medical clinics helps future psychologists better understand the specific needs and challenges involved in developing motivational systems. Practical training in such settings allows theoretical knowledge to be adapted to real-life situations, significantly improving the effectiveness of the motivational systems created. Future psychologists who had the opportunity to work in clinics demonstrated a high level of skill in addressing practical tasks related to staff motivation, highlighting the substantial contribution of hands-on experience to their training. The research emphasised the importance of integrating practical experience with theoretical instruction in the education of future psychologists, particularly in the context of developing and implementing motivational systems. Educators can utilise the findings to enhance training programmes and approaches to preparing future specialists, especially in the development of specialised courses and training in motivational counselling